Understanding the Significance of Cultural Branding in Brand Theory - Kayoko Honjo (Maketingu Janaru, 2020)
This article examines the understanding and significance of cultural branding of Holt, which is evaluated as a bridge between CCT and brand strategies. This task is performed while focusing on problem consciousness, perspective to brands and academic area on which to rely. The model is positioned as the interpretivism which deals with transcendent concepts for culture and brand, and its construction process complements traditional positivism and can be considered to provide strategic flexibility and practicality. It is also showed strong brands are more likely to be criticized by communities, so brand is not of the absolute property, but rather the ideal state of the brand that meets the managerial goal, constrained by environment and having a dynamic property.